The Compact Finite Difference Method of Two-Dimensional Cattaneo Model. (28th May 2020) - Huang, Yating; Yin, Zhe
Abstract : In this paper, we propose and analyze the compact finite difference scheme of the two-dimensional Cattaneo model. The stability and convergence of the scheme are proved by the energy method, the convergence orders are 2 in time and 4 in space. We also use the variables separation method to find the true solution of the problem. On this basis, the validity and accuracy of the scheme are verified by numerical experiments.